Development of OrSAEv Model Learning Materials Based on Role-Playing of Against Flood Disaster Mitigation Preparedness, Anxiety and Enjoyment of Junior High School - Novia W. Kusumaningrum; Madlazim; Tarzan Purnomo (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
This study aims to produce a OrSAEv model learning materials based on role-playing for effective disaster mitigation to improve flood disaster mitigation preparedness, identify anxiety and enjoyment in junior high school. This type of research is the four-Dodels. The research subjects were 29 students of grade VII at SMPN 2 Kalitidu. Based on the results of the analysis and discussion that has been carried out, it shows that the development of learning material are valid with the validity value of each Leson Plans 100%, Student Worksheet 98%, Student Book 94%, Test Questions 96%, Mitigation Questionnaire 100%, The Enjoyment Questionnaire 100%, and the Anxiety Questionnaire 100%. In addition, the learning tools that have been developed are also stated to be implemented measures based on the results of the implementation of the lesson plans from 3 meetings with 94.1%, 93.8% and 92.9%, respectively, for the student response questionnaire a score of 2.5 indicates that the students respond well. Student learning outcomes improve Based on the poster analysis, the criteria are quite good. The criteria for disaster mitigation simulation skills are quite good. The results of the enjoyment questionnaire showed that students did not enjoy it, while the anxiety questionnaire showed that students did not feel anxiety. Recommendations that can be given are pre-learning activities required, understanding the use of software, introduction to students about the orsaev learning model based role-playing.